The use of technologies in education: initial perceptions of teachers involved in the Edulab project - Oliveira, Ana (2019)
EduLab is an educational project which aims to promote innovative teaching practices through the use of technological resources. This paper reports the initial perceptions of the teachers involved in this project concerning the use of technologies in educational contexts. Teachers’ perceptions were collected at the beginning of the project, through the completion of a questionnaire. The data’s statistical analysis allows us to conclude that the thirteen involved teachers master a great part of digital functionalities, highlighting difficulties in the production of podcasts and videocasts, in the creation and implementation of wikis, eBooks and blogs and in the use of drawing and image editing tools. Teachers reported the usual use of digital technologies to prepare lessons. In this context, digital technologies were mostly used to search information on the Internet, to consult open educational resources, to prepare working proposals, presentations and students assessment, and to collaborate and communicate with other teachers. In the classroom, digital technologies were mostly used to search issues the Internet and access virtual learning books. The results sustain the thesis that the use of technologies in the educational process interests and motivates learners, allowing the development of "learn to learn" skills. However, some teachers disagree that the use of technologies encourages collaborative work and promotes more student-centred learning. The questionnaire results also showed that teachers recognize some barriers to the use of technology in education. Although the results are not consensual, the lack of training and technological knowledge of teachers, the lack of technological resources at school and the lack of time in classes are the main referred barriers.